Imperial to international a history of St. John's Cathedral, Hong Kong - Wolfendale, Stuart (Hong Kong : Hong Kong University Press, 2013)
Founded in 1849, St John's Cathedral is the oldest, neo-gothic cathedral in East Asia and China's oldest surviving, still-operating Anglican church. In its early decades, the cathedral was the center of Hong Kong colonial life. Today, it has drawn in other Hong Kong communities, becoming a truly international church with services in several languages. This first comprehensive history of St John's traces the cathedral's role as a colonial parish church and as a bishop's seat for a diocese stretching across China and beyond. It also discusses St John's significance as a center of modern worship.
Foreword / by Paul Kwong -- Introduction -- Genesis, 1841-1850 -- Imperial parish, 1850-1873 -- Quiescence and struggle, 1873-1906 -- The search for substance, 1902-1927 -- The making of a cathedral, 1927-1941 -- Out of darkness, 1941-1953 -- Shedding colonialism, 1953-1976 -- Towards an international church, 1976-1992 -- Into the 'Chinese century' -- Appendices -- 1. List of Chaplains, Deans and Bishops -- 2. List of Stipendiary Assistant Chaplains and Chaplains -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: St. John's Cathedral (Hong Kong, China); St. John's Cathedral (Hong Kong, China); Anglican Communion -- China -- Hong Kong -- History; Anglican church buildings -- China -- Hong Kong -- History; Christianity -- China -- Hong Kong; RELIGION -- Christianity -- Anglican; SOCIAL SCIENCE / Sociology of Religion; Electronic books